Self-Awareness and Higher Cognitive Functions: Exploring the Foundations of Human Consciousness - Muhammad Amir; Laiba shaiq; Muhammad Umer; Farooq Hasan; Imtiaz Mahmood Tahir; Ghulam Aysha Bibi; Muhammad Shakeel; Iftikhar Younis Mallhi; Shafqat Rasool; Areeba Iqbal; Fethi Ahmet Ozdemir; Gaweł Sołowski; et al. (Dialogue Social Science Review (DSSR), 2025)
Metacognitive awareness — the ability to monitor and regulate one's own learning processes — represents a fundamental mechanism through which learners optimize their academic performance. By enabling self-assessment of comprehension and identification of knowledge gaps, metacognition allows for strategic allocation of cognitive resources toward areas requiring improvement.This study examines the relationship between metacognitive development, self-awareness, and academic achievement, with particular focus on the neurobiological foundations of consciousness and their implications for educational outcomes.Theresearch investigated the interplay between higher-order cognitive processes, including memory consolidation, perceptual processing, and decision-making mechanisms, that underpin conscious awareness and self-reflective capacity. The findings demonstrate that enhanced metacognitive skills correlate with improved learning efficiency through targeted remediation of identified weaknesses. The development of self-awareness and reflective thinking capabilities strengthens both academic performance and interpersonal functioning by facilitating more effective decision-making processes.These results suggest that consciousness, defined as the capacity for self-reflective thought and emotional awareness, represents a critical determinant of educational success. The ability to monitor one's cognitive states and modify learning strategies accordingly appears to be mediated by complex interactions between memory systems, attentional networks, and executive control mechanisms. Keywords Thinking circuits, Thought monitoring, Retrospection, Comprehension, consciousness.